PENGARUH ATTANDANCE, DISCIPLINE, DAN LOST TIME PADA TINGGI RENDAHNYA OUTPUT LINE HIACE ROOF BACKDOOR Di PT X - Rahma Sarita; vitri Aprilla Handayani (JURNAL SINTAK, 2023)
This study aims to determine whether there is a significant effect on attendance, discipline and lost time on the high and low output line hiace roof backdoor at PT Sumitomo Wiring System Batam Indonesia. This study uses multiple Linear Regression Analysis Techniques. The type of data used in this study is primary data. This primary data was obtained from a questionnaire distributed to PT Sumitomo Wiring System Batam Indonesia employees. The results of this study significantly indicate that attendance, discipline, and lost time have an effect on the high or low output line hiace roof backdoor